Deficiency of GPI Glycan Modification by Ethanolamine Phosphate Results in Increased Adhesion and Immune Resistance of Aspergillus fumigatus - Ouyang, Haomiao; Zhang, Yi; Zhou, Hui; Ma, Yubo; Li, Ruoyu; Yang, Jinghua; Wang, Xiaowen; Jin, Cheng (Frontiers in Cellular and Infection Microbiology, 2021)
GPI anchored proteins play important roles in maintaining the function of the cell wall and participating in pathogenic processes. Addition and removal of phosphoethanolamine (EtN-P) on the second mannose residue in GPI anchor is vital for maturation and sorting of GPI anchored proteins. Previously, we have shown that deletion of the gpi7, the gene encodes an EtN-P transferase responsible for addition of EtN-P to the second mannose residue of GPI anchor, leads to mis-localization of GPI anchored proteins, abnormal polarity, reduced conidiation and fast germination in Aspergillus fumigatus. In this report the adherence and virulence of the A. fumigatus gpi7 deletion mutant were further investigated. The germinating conidia of the mutant exhibited an increased adhesion and a higher exposure of cell wall polysaccharides. Although the virulence was not affected, an increased adherence and a stronger inflammation response of the mutant were documented in immounocompromised mice model. In vitro assay confirmed that the Δgpi7 mutant induced stronger immune response and was more resistant to killing. Our findings, for the first time, demonstrate that in A. fumigatus GPI anchoring is required for proper organization of the conidial cell wall. Lacking of Gpi7 leads to fast germination, stronger immune response and resistance to macrophage killing.